Rimba ilmu extension - Rimba ilmu collaborative learning authoring tool (RICLAT) - Lim, Zi Xuan (Universiti Malaysia Sarawak, (UNIMAS), 2014)
Educator had face a brunch of challenges in educating the students. Student paying less attention during the lecture is one of the main challenge educator faced. Rimba Ilmu is one of the Single Display Groupware (SDG) which enable the collaborative activity with multiple device input. However, some limitations of Rimba Ilmu are there is a lacking of feature to enable teachers to create teaching material and also collaborative activities with self-designed content. An authoring tools is necessary to achieve collaborative activities creation. The objective for this system development is to design and develop an authoring tool that allows teachers to create classroom content and collaborative activities. This system is implemented with several module which are presentation work module, slide module, and media component module. These modules enable the creation of presentation work which includes slides with media component such as audio, image, and text. Besides, the creation of collaborative activity is available in this system together with creation of questions and answers. Total off lye mouse inputs are available in the collaborative activity generated by this system and it is performs in presentation mode of this system. The system test for this system shows that this system had met the requirement. Most of the teachers are able to create presentation work with collaborative activities and satisfy with this system. However, this system requires future enhancement for better user experience and greater interaction style templates.